2018
DOI: 10.15809/irriga.2016v21n2p257-268
|View full text |Cite
|
Sign up to set email alerts
|

Frequência Da Fertirrigação Fosfatada Na Produtividade Da Cultura Da Melancia

Abstract: FREQUÊNCIA DA FERTIRRIGAÇÃO FOSFATADA NA PRODUTIVIDADE DA CULTURA DA MELANCIA BENITO MOREIRA DE AZEVEDO1; CARLOS NEWDMAR VIEIRA FERNANDES2; JOAQUIM RAIMUNDO DO NASCIMENTO NETO3; THALES VINÍCIUS DE ARAÚJO VIANA1; DENISE VIEIRA VASCONCELOS3 E CHRISLENE NOJOSA DIAS FERNANDES3 [1]Departamento de Engenharia Agrícola, CCA/UFC, Av. Mister Hull, s/n, Bloco 804. Caixa Postal 12.168, Fortaleza, CE, Brasil, 60.455 970, benitoazevedo@hotmail.com, thales@ufc.br2Instituto Federal de Educação Ciência e Tecnologia do Ceará (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Research has shown that through by these methods, only plants use 1/3 of the nitrogen and potassium fertilizers incorporated into the soil, the rest is lost through leaching, surface runoff and volatilization (ANDRADE JUNIOR et al, 2006). On the other hand, the supply of fertilizers through irrigation water, compared to conventional fertilization, opens new possibilities for better control of the nutritional needs of crops (AZEVEDO et al, 2016), especially in areas where irrigation represents the main method of water supply. Camargo et al (2012) state that the application of K by fertigation, especially under a localized irrigation system, has been growing significantly, since it can be applied directly where there are a greater number of roots, in order to facilitate its absorption by plants, reducing losses by leaching, which consequently reflects in higher yields to the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that through by these methods, only plants use 1/3 of the nitrogen and potassium fertilizers incorporated into the soil, the rest is lost through leaching, surface runoff and volatilization (ANDRADE JUNIOR et al, 2006). On the other hand, the supply of fertilizers through irrigation water, compared to conventional fertilization, opens new possibilities for better control of the nutritional needs of crops (AZEVEDO et al, 2016), especially in areas where irrigation represents the main method of water supply. Camargo et al (2012) state that the application of K by fertigation, especially under a localized irrigation system, has been growing significantly, since it can be applied directly where there are a greater number of roots, in order to facilitate its absorption by plants, reducing losses by leaching, which consequently reflects in higher yields to the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that through by these methods, only plants use 1/3 of the nitrogen and potassium fertilizers incorporated into the soil, the rest is lost through leaching, surface runoff and volatilization (ANDRADE JUNIOR et al, 2006). On the other hand, the supply of fertilizers through irrigation water, compared to conventional fertilization, opens new possibilities for better control of the nutritional needs of crops (AZEVEDO et al, 2016), especially in areas where irrigation Coletânea Internacional de Pesquisa em Ciências Aplicadas e Ciências Exatas Vol. 01 -Fotobiomodulação no tratamento de necrose de língua em cão 279 represents the main method of water supply.…”
Section: Introductionmentioning
confidence: 99%
“…The supply of fertilizers through irrigation water opens up new possibilities for a better control of the nutritional needs of crops. (Azevedo et al, 2016). The response of melancholy to nitrogen depends on the applied dose, form of fertilizer application (manual application or fertirrigation), cultivar and soil and climatic conditions of the experiment, being common indications of N, ranging from 80 to 300 kg ha -1 (Morais et al, 2008;Araújo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%